Antano Zemlicko antikvarinis knygynas Vilniuje 1942–1944 m. - Zemlickienė, Stefanija (Knygotyra, 1995)
This article is founded on Jadvyga Zemlickienės and Eugenijus Matuzevičius reminiscences.A. Zemlickas and E. Matuzevičius composed a joint stock, company “Knyga” at the end of 1941 and at the beginning of 1942. A Lithuanian bookshop with publishing rights was planned to open in Vokiečių street 26. The greatest difficulty was to receive the permission from german occupational regime to open such a bookshop. The bookshop was opened in spring 1942, without an official permission. The principal aim was to accumulate as many Lithuanian books as it was possible.The fate predicted not long existence for this book-propagation centre. In the summer of 1944 the house was burnt down, and very few books were saved.Antanas Zemlickas’ bookshop united Lithuanian intelligentsia in war time and played an important educational role. It reflected Vilnius and Vilnius district features such as the preservation of Lithuanianism and Lithuanian-Polish relations.